The role of preservation on the quantification of morphology and patterns of disparity within Paleozoic echinoderms. (28th February 2017) - Deline, Bradley; Thomka, James R.
Abstract: The loss of information resulting from taphonomic degradation could represent a significant bias in the study of morphological diversity. This potential bias is even more concerning given the uneven effect of taphonomy across taxonomic groups, depositional facies, and stratigraphic successions and in response to secular changes through the Phanerozoic. The effect of taphonomic degradation is examined using character-based morphological data sets describing disparity in Paleozoic crinoids and blastozoans. Characters were sequentially excluded from the analyses following progressive taphonomic loss to determine how morphologic metrics, such as the relative distribution of taxa in morphospace and partial disparity, changed with increasing taphonomic alteration. Blastozoans showed very little change in these metrics with decreasing preservational quality, which is a result of characters that create distance in morphospace being recognizable in isolated plates. The opposite result is present in crinoids as the characters that are important in structuring the morphospace require intact modules (i.e., the calyx) to accurately assess. Temporal and stratigraphic trends produced encouraging results in that patterns could be largely recovered even with exaggerated taphonomic biases. However, certain parts of a stratigraphic sequence should be avoided and morphological outliers could potentially play a larger role through time, though both of these biases can be easily identified and avoided. The methods presented in this study provide a way to assess potential taphonomic biases in character-based studies of morphological diversity.